Thermal microrefugia and changing climate affect migratory phenology of a thermally constrained marine mammal - Hieb, Elizabeth E.; Cloyed, Carl S.; DaCosta, Kayla P.; Garelick, Angela; Carmichael, Ruth H. (Frontiers in Ecology and Evolution, 2023)
Changing climate conditions are well documented to affect species distribution patterns and migratory phenology, especially for thermally constrained species. Climate induced changes and other natural and anthropogenic factors may affect habitats heterogeneously, altering microhabitats that act as refugia. Here, we used a thermally constrained marine mammal, the West Indian manatee (Trichechus manatus), as a model species to examine how the availability of thermal microrefugia combined with climate driven increases in regional water temperatures may affect the timing and duration of occurrence at the northern margins of the species' range.We used aerial, thermographic imaging to identify potential thermal anomalies that could act as thermal microrefugia for manatees during unfavorable cold temperatures and assessed manatee occurrence at these sites using citizen-sourced manatee sightings and stranding response data.To further understand how regional and longer-term water temperatures may affect the use of thermal microrefugia and phenology of migration, we compared spatial and temporal distributions of manatee sightings to air and sea surface temperatures on a decadal scale.Thermal anomalies were detected at various sources, and documented manatee sightings at or near these sites support use as thermal microrefugia during cold periods. Cold season manatee sightings at a known western migratory endpoint (Alabama waters) have increased during the last decade, primarily through increased sightings during the late fall and early winter (Nov -Jan) that correspond to increased regional temperatures during the same period. Manatees may use thermal microrefugia to remain at northern latitudes longer, delaying seasonal migrations or overwintering as conditions allow. Climate change is likely to have further effects on the species' distribution and migration patterns, potentially facilitating modern range expansion that has implications for management and recovery actions for manatees across their range. Our study provides novel insight for manatees but may also be used as a model to understand how other thermally constrained species may expand their ranges into higher latitudes.